Understanding the Use and Efficacy of Moderate Stringency DNA Searches, United States, 2018 - Piquado, Tepring ([Verlag nicht ermittelbar], 2023)
This study was undertaken to investigate familial DNA and moderate stringency DNA testing practices and to highlight the policy development, associated costs, limitations, and capabilities that DNA testing provides in order to offer relevant insight to criminal justice and law enforcement policymakers and researchers who are interested in the use of DNA testing to solve and deter crime.